Jade color-changing ceramic dry granular glaze, ceramic tile and preparation method of ceramic tile
By introducing variable color-changing dry particles and silver halide into the ceramic glaze layer, the automatic color-changing effect of the ceramic tile glaze layer is achieved by using light and heat-induced effects, and the problem of the fixed jade effect of the existing ceramic tile glaze layer is solved. , improves the decorativeness.
Patent Information
- Application Number
- CN202411405573.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The jade effect of the existing ceramic tile glaze layer is fixed after firing, and cannot automatically change color when the environment changes such as light and heat, and lacks a changing visual effect.
The jade dry particles are introduced that can change with light or heat. The Ag+ colloid is formed by the ultraviolet light decomposition of silver halide, occupying large voids formed by the distortion of boron element, forming a larger scattering micro-region with micro-nano crystals, changing The transparency and jade effect of the glaze layer; after heating, Ag+ is recombined to restore the transparent effect of the glaze layer.
The different jade effects of ceramic glaze layer under environmental changes have been achieved, enriching the decorative properties of ceramic products.
Smart Images

Figure BDA0005076461820000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building ceramics, and in particular relates to a jade-like color-changing ceramic dry granular glaze, a ceramic tile and a preparation method thereof. Background Art
[0002] The various styles of expression in architectural ceramics are often closely related to the corresponding design patterns and glaze layers. The overall display effect of ceramic tiles is achieved by combining the design of specific patterns with the thickness of the glaze layer, the transparency of the glaze layer, and the glossiness of the glaze layer surface. At present, the glaze layer of ceramic tiles is mainly formed through the following ways: ① After the minerals are directly configured, wet ball milling is performed to form a slurry and applied to the pattern layer; ② Part of the raw materials in the minerals are pre-made into a glassy state and water-quenched and crushed to form a corresponding frit or dry granules, and then wet ball milled with other minerals to form a slurry and applied to the pattern layer; ③ The mineral components and functional components are made into glassy state and water-quenched and crushed to form a corresponding frit or dry granules, and then the corresponding glazing method (glue dry granules, dry stacking, wet stacking, high-pressure glaze spraying, digital glaze spraying, etc.) is used to form a glaze layer on the pattern layer; finally, the green bodies prepared by these methods are fired to obtain semi-finished ceramic tiles.
[0003] Through the preparation of dry particles, some special components that may react with certain mineral components in the glaze can be solidified or crystallized, so as to achieve the aesthetic and functionalization of the glaze on the ceramic tile. Jade in nature, such as jadeite, Hetian jade, agate, Xiuyan jade, and Dushan jade, have become reference objects for the glaze effect on the surface of ceramic tiles. The transparency and semi-transparency of their materials are a way to control the jade effect of the glaze layer on the surface of ceramic tiles. However, the jade effect of the glaze layer of ceramic tiles is often determined when they are fired, that is, their transparency and jade effect are fixed.
[0004] Therefore, there is an urgent need to develop a ceramic glaze that can change color and automatically change the jade texture of the glaze layer when the external environment such as light and heat changes, giving it a changing visual effect. Summary of the invention
[0005] The present invention provides a jade-like color-changing ceramic dry granular glaze, a ceramic tile and a preparation method thereof, so as to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.
[0006] The inventive concept of the present invention is: by introducing color-changing dry particles that can change with light or heat into specific jade dry particles, the micro-nano crystals dispersed in the jade dry particles form a jade semi-transparent effect, and the silver halide in the color-changing dry particles is decomposed by ultraviolet light to form dispersed Ag +The colloid preferentially occupies the large voids formed by the distortion of the boron element in the discolored blank, and forms larger scattering micro-regions with the micro-nano crystals in the jade dry particles, increasing the opacity of the glaze layer and reducing its transparency, thereby changing the jade effect of the glaze layer. After being heated at low temperature, the dispersed Ag + The colloids are separated from the large voids and recombined with the halogen ions, reducing the size of the dispersed micro-regions in the glaze layer and restoring the translucent effect of the glaze layer. This achieves the jade-like effect of the glaze layer changing color with the environment, enriching the decorativeness of the ceramic products.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a ceramic dry particle glaze, wherein the raw material components include jade dry particles and color-changing dry particles, wherein the jade dry particles are barium feldspar-type jade dry particles (jade dry particles with barium feldspar as the main crystallization phase), and the content of BaO in the chemical composition of the jade dry particles is 5-10wt%;
[0008] The chemical composition of the color-changing dry particles includes, by weight percentage, 55.00-58.00% SiO2, 14.00-17.00% Al2O3, 0.01-0.03% Fe2O3, 0.01-0.05% TiO2, 5.00-7.00% CaO, 1.00-2.00% MgO, 3.50-4.50% K2O, 1.50-3.00% Na2O, 4.00-7.00% B2O3, 0.05-0.20% ZrO2, 1.50-3.00% ZnO, 1.50-3.00% BaO, 1.00-2.00% SrO, 0.20-0.80% silver halide, and 0.05-0.20% loss on ignition.
[0009] Specifically, after firing, the size of the diffusion point of the common jade dry particles for visible light scattering is fixed, and will not change with the change of environment in the later use process, so the jade effect will not change. The present invention increases the content of BaO in the components of the jade dry particles to form a jade effect containing micro-nano crystals such as sodium barium feldspar and potassium barium feldspar. The glaze layer made of the jade dry particles forms a translucent jade state after firing. At the same time, in the color-changing dry particles containing boron oxide, due to B 3+ (4 coordination: ) has a radius greater than Si under the same coordination 4+ (4 coordination: ) and Al 3+ (4 coordination: ) is small, it is easier to distort the gap formed by oxygen atoms with the same coordination number, and B 3+ As a network former, with Si 4+Compared with the traditional method, the electricity price is more likely to cause the formation of disconnected structure, resulting in the appearance of large gaps; the ultraviolet light induces the silver halide, based on AgX→Ag + +X - Reaction (X represents halogen), Ag in silver halide + Ions are free and aggregated into Ag + Colloidal particles, Ag agglomerated + Colloidal particles occupy large gaps and become diffusion points in the visible light wavelength range. The diffusion points and micro-nano crystals work together to form larger diffusion micro-regions, increasing the scattering effect of the glaze layer on light and enhancing the opacity of the glassy glaze layer, thereby reducing the transparency of the jade-like glaze layer and changing the jade-like effect of the glaze layer. + Reconnect with X - Combined with the large gaps around the boron element, the scattering effect of the glaze layer on light is reduced, the transparency of the glaze layer is increased, and ultimately the transformation of the glaze layer to different jade effects under environmental changes is achieved.
[0010] Preferably, the chemical composition of the celsium feldspar-type jade dry particles includes, by weight percentage: 56.00-61.00% SiO2, 16.00-18.00% Al2O3, 0.01-0.03% Fe2O3, 0.01-0.05% TiO2, 1.50-2.50% CaO, 1.00-2.00% MgO, 3.50-4.50% K2O, 3.50-4.50% Na2O, 0.05-0.20% ZrO2, 2.50-3.50% ZnO, 6.50-9.00% BaO, 1.00-2.00% SrO, and 0.05-0.20% loss on ignition.
[0011] Preferably, the mass ratio of the jade-like dry particles to the color-changing dry particles is (7-22):1.
[0012] Preferably, the silver halide is AgBr or AgI.
[0013] Preferably, the preparation steps of the jade dry particles include:
[0014] The raw materials for preparing the jade dry particles are mixed, melted at 1400-1450° C. for 8-10 hours, poured into water for quenching to obtain jade frit particles, and then crushed to obtain the jade dry particles.
[0015] Preferably, the particle size of the jade dry particles is between 58-106 μm.
[0016] Preferably, the preparation step of the color-changing dry particles comprises: mixing the raw materials for preparing the color-changing dry particles, melting at 1300-1400° C. for 8-10 hours, pouring into water for quenching to obtain color-changing frit particles, and crushing to obtain the color-changing dry particles.
[0017] Preferably, the particle size of the color-changing dry particles is between 45-75 μm. The particle size of the color-changing dry particles is smaller than that of the jade dry particles, so that they can be evenly dispersed around the jade dry particles, so that they can be evenly dispersed between the micro-nano crystals such as sodium barium feldspar and potassium barium feldspar in the jade dry particles after firing.
[0018] The second aspect of the present invention provides a ceramic tile, which includes, from bottom to top, a body layer, a surface glaze layer, a pattern layer, a dry granular glaze layer and a protective glaze layer, the dry granular glaze layer includes a color change area and a jade area, the color change area is formed by firing the above-mentioned ceramic dry granular glaze; the jade area is formed by firing the jade dry particles.
[0019] Preferably, the color-changing areas are distributed in the jade area in the form of dots, lines or blocks.
[0020] A third aspect of the present invention provides a method for preparing a ceramic tile, comprising the following steps:
[0021] Taking the raw material of the green body layer to obtain the green body layer;
[0022] Mixing jade dry particles, color-changing dry particles, glue and water to obtain color-changing dry particle glaze slurry;
[0023] Mixing jade dry particles, glue and water to obtain jade dry particle glaze slurry;
[0024] Respectively taking raw materials of the surface glaze layer and the protective glaze layer to prepare the surface glaze slurry and the protective glaze slurry;
[0025] The surface glaze slurry is applied on the surface of the green body layer in sequence, a pattern is inkjet printed, the jade-like dry granular glaze slurry, the color-changing dry granular glaze slurry and the protective glaze slurry are applied, and after drying and firing, the ceramic tile is obtained.
[0026] Preferably, the glue is a mixture of polyvinyl acetate, polyethylene glycol, acrylate polymer, and propylene glycol block copolymer in a mass ratio of (3-5): (1-3): (10-13): (6-10); the flow rate range measured using a coating-4 cup is 55-85 seconds, and the glue viscosity range measured by a rotational viscometer is 900-1100 mPa·s.
[0027] Preferably, in the color-changing dry particle glaze slurry, the mass ratio of jade dry particles, color-changing dry particles, glue and water is (7-22):1:(10-20):(3-10).
[0028] Preferably, the specific gravity of the color-changing dry granular glaze slurry is 1.45-1.55 g / cm 3 .
[0029] Preferably, in the jade dry particle glaze slurry, the mass ratio of jade dry particles, glue and water is 1:(0.7-1):(0.3-0.7).
[0030] Preferably, the specific gravity of the jade dry granular glaze slurry is 1.45-1.55 g / cm 3 .
[0031] Preferably, the chemical composition of the green body layer includes, by mass percentage: 66.00-72.00% SiO2, 18.20-20.10% Al2O3, 0.20-0.40% Fe2O3, 0.10-0.30% TiO2, 0.30-1.00% CaO, 0.10-0.50% MgO, 2.40-2.80% K2O, 3.20-3.70% Na2O, and 4.00-4.80% loss on ignition.
[0032] Preferably, the chemical composition of the glaze layer includes, by mass percentage: 48.50-54.00% SiO2, 33.00-37.50% Al2O3, 0.05-0.15% Fe2O3, 0.30-0.50% TiO2, 0.80-1.20% CaO, 0.30-0.50% MgO, 0.70-1.20% K2O, 4.00-4.80% Na2O, 0.30-0.50% ZrO2, 1.50-2.50% ZnO, and 2.00-3.00% loss on ignition.
[0033] Preferably, the specific gravity of the glaze slurry is 1.85-1.95 g / cm 3 .
[0034] Preferably, the chemical composition of the protective glaze layer includes, by mass percentage: 48.0-53.0% SiO2, 19.0-22.0% Al2O3, 0.30-0.50% Fe2O3, 0.10-0.30% TiO2, 5.50-7.50% CaO, 1.00-1.70% MgO, 4.0-5.0% K2O, 1.0-3.0% Na2O, 0.30-0.50% ZrO2, 3.0-5.0% ZnO, and 9.0-13.0% loss on ignition.
[0035] Preferably, the specific gravity of the protective glaze slurry is 1.35-1.45 g / cm 3 .
[0036] Preferably, the maximum sintering temperature is 1170-1210°C.
[0037] Preferably, the firing cycle is 55-65 minutes.
[0038] Preferably, the sintering is carried out at a maximum sintering temperature for a holding time of 7 to 15 minutes.
[0039] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0040] (1) The ceramic dry particle glaze of the present invention comprises jade dry particles and color-changing dry particles. The content of BaO is increased in the components of the jade dry particles to form translucent jade sodium barium feldspar, potassium barium feldspar and other micro-nano crystals in the glaze layer; at the same time, boron oxide and silver halide are introduced into the color-changing dry particles. The silver halide is decomposed by ultraviolet light to form large voids, and the dispersed Ag + The colloid preferentially occupies the large gaps formed by the distortion of the boron element, and forms larger scattering micro-regions with the micro-nano crystals in the jade dry particles, increasing the opacity of the glaze layer and reducing the transparency of the glaze layer, thereby changing the jade effect of the glaze layer. + Reconnect with X - Combined with the large gaps around the boron element, the scattering effect of the glaze layer on light is reduced, the transparency of the glaze layer is increased, and ultimately the transformation of the glaze layer to different jade effects under environmental changes is achieved.
[0041] (2) The present invention introduces color-changing dry particles that can change color when exposed to light or heat into specific jade dry particles. The color-changing dry particles can change the transparency of a part of the glaze layer. Combined with the colored dry particles in the glaze layer, the present invention finally achieves a jade effect in which the glaze layer presents different colors and transparencies as the environment changes, thereby enriching and enhancing the decorative effect of the jade ceramic tile. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0043] The chemical composition of the blank used in the embodiments of the present invention and the comparative examples includes, by mass percentage, 68.25% SiO2, 19.34% Al2O3, 0.31% Fe2O3, 0.26% TiO2, 0.76% CaO, 0.34% MgO, 2.73% K2O, 3.53% Na2O, and 4.48% loss on ignition.
[0044] The chemical composition of the glaze layer includes, by mass percentage, 52.48% SiO2, 34.68% Al2O3, 0.12% Fe2O3, 0.39% TiO2, 1.08% CaO, 0.44% MgO, 1.12% K2O, 4.62% Na2O, 0.37% ZrO2, 2.08% ZnO, and 2.62% loss on ignition.
[0045] The chemical composition of the protective glaze layer includes, by mass percentage, 51.35% SiO2, 20.53% Al2O3, 0.39% Fe2O3, 0.18% TiO2, 6.23% CaO, 1.48% MgO, 4.37% K2O, 2.13% Na2O, 0.41% ZrO2, 3.65% ZnO, and 9.28% loss on ignition.
[0046] The glue is a mixture of polyvinyl acetate, polyethylene glycol, acrylate polymer and propylene glycol block copolymer in a mass ratio of 2:1:6:4; the flow rate range measured by using a coating-4 cup is 55-85 seconds, and the viscosity range of the glue measured by a rotational viscometer is 900-1100 mPa·s.
[0047] Example 1
[0048] A ceramic dry particle glaze, whose raw material components include jade dry particles and color-changing dry particles.
[0049] Among them: the chemical composition of the color-changing dry particles, by weight percentage, includes: 56.35% SiO2, 16.72% Al2O3, 0.02% Fe2O3, 0.04% TiO2, 6.58% CaO, 1.36% MgO, 3.74% K2O, 1.96% Na2O, 6.41% B2O3, 0.09% ZrO2, 2.05% ZnO, 2.77% BaO, 1.24% SrO, 0.51% AgBr, 0.16% loss on ignition; the particle size D90 of the color-changing dry particles is 64μm.
[0050] The chemical composition of the jade dry particles includes, by weight percentage, 58.42% of SiO2, 17.15% of Al2O3, 0.02% of Fe2O3, 0.03% of TiO2, 1.83% of CaO, 1.78% of MgO, 4.07% of K2O, 3.95% of Na2O, 0.11% of ZrO2, 3.22% of ZnO, 7.58% of BaO, 1.75% of SrO, and 0.09% of loss on ignition; the particle size D90 of the jade dry particles is 90 μm.
[0051] A method for preparing a ceramic tile comprises the following steps:
[0052] (1) weighing and mixing raw materials of jade dry particles according to chemical composition, melting at 1400° C. for 9 hours, and then pouring into water for quenching to obtain fused particles; then grinding the fused particles to obtain jade dry particle powder;
[0053] (2) weighing and mixing the raw materials of the color-changing dry particles according to the chemical composition, melting them at 1300° C. for 8 hours, then pouring them into water and quenching them to obtain frit particles; then grinding the frit particles to obtain color-changing dry particle powder;
[0054] (3) The jade dry powder obtained in step (1), the color-changing dry powder obtained in step (2), glue and water are mixed in a mass ratio of 15:1:16:8 to obtain a specific gravity of 1.52 g / cm 3 Color-changing dry granular glaze slurry;
[0055] (4) The jade dry powder obtained in step (1), glue and water are mixed in a mass ratio of 1:0.9:0.6 to obtain a specific gravity of 1.51 g / cm 3 Jade dry granular glaze slurry;
[0056] (5) According to the chemical composition, the raw materials of the glaze layer were weighed, and water (the mass ratio of the material to the water was 100:39) was added to the ball mill. After screening and iron removal, the specific gravity was 1.91 g / cm 3 glaze slurry;
[0057] (6) According to the chemical composition, the raw materials of the protective glaze layer were weighed, and water (the mass ratio of the raw materials to the water was 100:61) was added to the ball mill. After screening and iron removal, the specific gravity was 1.41 g / cm 3 Protective glaze slurry;
[0058] (7) Apply the glaze slurry prepared in the above steps on the surface of the green body layer (the glaze amount is 705g / m 2 ), inkjet print pattern; then according to the preset pattern, use digital glaze spraying to apply jade dry granular glaze slurry and color-changing dry granular glaze slurry; finally spray protective glaze slurry (spraying amount is 64g / m 2), dried, and fired at 1195°C for 59 minutes (the holding time at the highest firing temperature is 9 minutes) to obtain the ceramic tile of this embodiment.
[0059] Example 2
[0060] A ceramic dry particle glaze, whose raw material components include jade dry particles and color-changing dry particles.
[0061] Among them: the chemical composition of the color-changing dry particles, by weight percentage, includes: 56.26% SiO2, 16.43% Al2O3, 0.02% Fe2O3, 0.04% TiO2, 6.75% CaO, 1.42% MgO, 3.86% K2O, 2.05% Na2O, 6.21% B2O3, 0.11% ZrO2, 2.24% ZnO, 2.48% BaO, 1.32% SrO, 0.65% AgI, 0.16% loss on ignition; the particle size D90 of the color-changing dry particles is 60μm.
[0062] The chemical composition of the jade dry particles includes, by weight percentage, 59.15% SiO2, 16.52% Al2O3, 0.02% Fe2O3, 0.03% TiO2, 1.92% CaO, 1.48% MgO, 4.08% K2O, 4.05% Na2O, 0.13% ZrO2, 2.77% ZnO, 8.07% BaO, 1.69% SrO, and 0.09% loss on ignition; the particle size D90 of the jade dry particles is 93 μm.
[0063] A method for preparing a ceramic tile comprises the following steps:
[0064] (1) weighing and mixing raw materials of jade dry particles according to chemical composition, melting at 1420° C. for 9 hours, pouring into water and quenching to obtain fused particles; then grinding the fused particles to obtain jade dry particle powder;
[0065] (2) weighing and mixing the raw materials of the color-changing dry particles according to the chemical composition, melting them at 1350° C. for 9 hours, and then pouring them into water for quenching to obtain frit particles; then grinding the frit particles to obtain the color-changing dry particle powder;
[0066] (3) The jade dry powder obtained in step (1), the color-changing dry powder obtained in step (2), glue and water are mixed in a mass ratio of 21:1:20:9.5 to obtain a specific gravity of 1.55 g / cm 3 Color-changing dry granular glaze slurry;
[0067] (4) The jade dry powder obtained in step (1), glue and water are mixed in a mass ratio of 1:0.88:0.6 to obtain a specific gravity of 1.54 g / cm 3 Jade dry granular glaze slurry;
[0068] (5) According to the chemical composition, the raw materials of the glaze layer were weighed, and water (the mass ratio of the material to the water was 100:39) was added to the ball mill. After screening and iron removal, the specific gravity was 1.91 g / cm 3 glaze slurry;
[0069] (6) According to the chemical composition, the raw materials of the protective glaze layer were weighed, and water (the mass ratio of the raw materials to the water was 100:61) was added to the ball mill. After screening and iron removal, the specific gravity was 1.41 g / cm 3 Protective glaze slurry;
[0070] (7) Apply the glaze slurry prepared in the above steps on the surface of the green body layer (the glaze amount is 705g / m 2 ), inkjet print pattern; then according to the preset pattern, jade dry granular glaze slurry and color-changing dry granular glaze slurry are applied by digital glaze spraying; finally, protective glaze slurry is sprayed (the spraying amount is 66g / m 2 ), dried, and fired at 1200°C for 56 minutes (the holding time at the highest firing temperature is 8 minutes) to obtain the ceramic tile of this embodiment.
[0071] Example 3
[0072] A ceramic dry particle glaze, whose raw material components include jade dry particles and color-changing dry particles.
[0073] Among them: the chemical composition of the color-changing dry particles, by weight percentage, includes: 55.42% SiO2, 16.83% Al2O3, 0.02% Fe2O3, 0.04% TiO2, 6.84% CaO, 1.61% MgO, 3.95% K2O, 2.15% Na2O, 6.83% B2O3, 0.08% ZrO2, 1.83% ZnO, 2.68% BaO, 1.38% SrO, 0.25% AgBr, 0.09% loss on ignition; the particle size D90 of the color-changing dry particles is 63μm.
[0074] The chemical composition of the jade dry particles includes, by weight percentage, 57.62% SiO2, 16.65% Al2O3, 0.03% Fe2O3, 0.04% TiO2, 2.13% CaO, 1.69% MgO, 4.21% K2O, 4.13% Na2O, 0.14% ZrO2, 3.33% ZnO, 8.27% BaO, 1.64% SrO, and 0.12% loss on ignition; the particle size D90 of the jade dry particles is 95 μm.
[0075] A method for preparing a ceramic tile comprises the following steps:
[0076] (1) weighing and mixing raw materials of jade dry particles according to chemical composition, melting at 1450° C. for 8 hours, and then pouring into water for quenching to obtain fused particles; then grinding the fused particles to obtain jade dry particle powder;
[0077] (2) weighing and mixing the raw materials of the color-changing dry particles according to the chemical composition, melting them at 1400° C. for 8 hours, then pouring them into water for quenching to obtain frit particles; then grinding the frit particles to obtain color-changing dry particle powder;
[0078] (3) The jade dry powder obtained in step (1), the color-changing dry powder obtained in step (2), glue and water are mixed in a mass ratio of 18:1:19:6 to obtain a specific gravity of 1.53 g / cm 3 Color-changing dry granular glaze slurry;
[0079] (4) The jade dry powder obtained in step (1), glue and water are mixed in a mass ratio of 1:1:0.52 to obtain a specific gravity of 1.50 g / cm 3 Jade dry granular glaze slurry;
[0080] (5) According to the chemical composition, the raw materials of the glaze layer were weighed, and water (the mass ratio of the material to the water was 100:39) was added to the ball mill. After screening and iron removal, the specific gravity was 1.91 g / cm 3 glaze slurry;
[0081] (6) According to the chemical composition, the raw materials of the protective glaze layer were weighed, and water (the mass ratio of the raw materials to the water was 100:62) was added to the ball mill. After screening and iron removal, the specific gravity was 1.39 g / cm 3 Protective glaze slurry;
[0082] (7) Apply the glaze slurry prepared in the above steps on the surface of the green body layer (the glaze amount is 708g / m 2 ), inkjet print pattern; then according to the preset pattern, jade dry granular glaze slurry and color-changing dry granular glaze slurry are applied by digital glaze spraying; finally, protective glaze slurry is sprayed (the spraying amount is 68g / m 2 ), dried, and fired at 1185°C for 64 minutes (the holding time at the highest firing temperature is 14 minutes) to obtain the ceramic tile of this embodiment.
[0083] Comparative Example 1
[0084] The only difference between Comparative Example 1 and Example 1 is that the ceramic dry particle glaze of Comparative Example 1 does not contain color-changing dry particles, but only jade dry particles.
[0085] Comparative Example 2
[0086] The difference between Comparative Example 2 and Example 1 is only that the chemical composition of the jade dry particles is different. The chemical composition of the jade dry particles in the ceramic dry particle glaze of Comparative Example 2 includes, by weight percentage: 57.78% SiO2, 17.31% Al2O3, 0.03% Fe2O3, 0.04% TiO2, 7.83% CaO, 2.12% MgO, 3.96% K2O, 3.82% Na2O, 0.14% ZrO2, 3.18% ZnO, 1.58% BaO, 2.08% SrO, and 0.13% loss on ignition.
[0087] Comparative Example 3
[0088] The difference between Comparative Example 3 and Example 1 is only that the chemical composition of the color-changing dry particles is different. The chemical composition of the color-changing dry particles in the ceramic dry particle glaze of Comparative Example 3 includes, by weight percentage: 57.35% SiO2, 16.78% Al2O3, 0.02% Fe2O3, 0.05% TiO2, 6.78% CaO, 2.36% MgO, 4.34% K2O, 4.16% Na2O, 0.11% ZrO2, 3.32% ZnO, 2.77% BaO, 1.24% SrO, 0.56% AgBr, and 0.16% loss on ignition.
[0089] Comparative Example 4
[0090] The difference between Comparative Example 4 and Example 1 is that the particle sizes of the color-changing dry particles and the jade dry particles are different. In Comparative Example 4, the particle size D90 of the color-changing dry particles is 96 μm; the particle size D90 of the jade dry particles is 90 μm.
[0091] Performance Testing
[0092] 1. Transmittance
[0093] According to the test requirements of the ultraviolet visible spectrophotometer in the standard "GB / T 2680-2021 Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet transmittance and related window glass parameters of architectural glass", the measurement wavelength range is 400-2000nm, and the ceramic dry granular glaze samples prepared in the above embodiments 1-3 and comparative examples 1-3 are tested for transmittance performance. The measuring equipment is a Japanese Shimadzu UV-1800 ultraviolet visible spectrophotometer, and the measured sample is a 2mm thick double-sided mirror polished sample at a wavelength of 750nm (red light). The results are shown in Table 1.
[0094] Table 1:
[0095] sample Transmittance (%) Transmittance after UV treatment (%) Example 1 51.96 34.30 Example 2 51.16 33.67 Example 3 53.75 36.24 Comparative Example 1 54.37 53.95 Comparative Example 2 76.35 68.55 Comparative Example 3 28.26 26.46
[0096] It can be seen from Table 1 that the transmittance of the samples prepared in Examples 1-3 all decreased significantly before and after ultraviolet light irradiation, indicating that the effect of ultraviolet light on silver halide significantly increased the scattering area in the glaze layer. Among them: Example 2 is similar to Example 1 in that silver bromide is replaced by silver iodide. Example 3 is slightly improved in transmittance by reducing the content of silver bromide relative to Example 1.
[0097] Since the ceramic dry particle glaze of Comparative Example 1 does not contain color-changing dry particles, the transparency of the glaze layer does not change significantly before and after ultraviolet light irradiation.
[0098] Since the BaO content in the jade dry particles of Comparative Example 2 is relatively low, the transparency of the glaze layer is significantly improved, indicating that the crystals in the glaze layer are reduced.
[0099] Since the color-changing dry particles of Comparative Example 3 do not contain B2O3 and only use silver bromide as a colorant, the transparency of the glaze layer does not change significantly before and after ultraviolet light irradiation.
[0100] 2. Color change performance
[0101] Using the American X-Rite Ci64 colorimeter, according to the standard "GB / T 36142-2018 Measurement method of color and color difference of architectural glass", the glaze surface of the ceramic tile samples prepared in the above Example 1 and Comparative Examples 1-4 was tested before and after ultraviolet light irradiation and 3 minutes before and after hot water splashing. The results are shown in Table 2.
[0102] Table 2:
[0103]
[0104] It can be seen from Table 2 that after the ceramic tile sample prepared in Example 1 was irradiated with ultraviolet light, the yellow color became significantly darker and the milky feeling was obvious; after being splashed with hot water, the sample returned to a light yellow, transparent and crystal effect.
[0105] Since the ceramic dry particle glaze of Comparative Example 1 does not contain color-changing dry particles, the glaze layer presents a milky white jade effect. After being irradiated with ultraviolet light, no color change effect occurs; and after being splashed with hot water, no obvious change occurs.
[0106] Since the BaO content in the jade dry particles of Comparative Example 2 is low, the transparency of the glaze layer is increased and it does not have a jade effect; after ultraviolet irradiation, the glaze layer changes from light yellow to light gray. Due to the enhanced light penetration ability, the light gray can return to light yellow after a period of time. After being splashed with hot water, there is no obvious change compared with before splashing.
[0107] Since the color-changing dry particles of Comparative Example 3 do not contain B2O3 and only use silver bromide as a colorant, the color of the glaze layer does not change significantly before and after ultraviolet light and before and after hot water is sprayed.
[0108] In Comparative Example 4, since the particle size of the color-changing dry particles is close to that of the jade dry particles, the area of the color-changing dry particles becomes larger, affecting the distribution of color in the glaze layer and forming a mottled area in the milky white transparent glaze layer.
[0109] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A ceramic dry granular glaze, characterized in that: The raw material components include jade dry particles and color-changing dry particles, wherein the jade dry particles are barium feldspar-type jade dry particles, and the content of BaO in the chemical composition of the jade dry particles is 5-10wt%; The chemical composition of the color-changing dry particles includes, by weight percentage, 55.00-58.00% SiO2, 14.00-17.00% Al2O3, 0.01-0.03% Fe2O3, 0.01-0.05% TiO2, 5.00-7.00% CaO, 1.00-2.00% MgO, 3.50-4.50% K2O, 1.50-3.00% Na2O, 4.00-7.00% B2O3, 0.05-0.20% ZrO2, 1.50-3.00% ZnO, 1.50-3.00% BaO, 1.00-2.00% SrO, 0.20-0.80% silver halide, and 0.05-0.20% loss on ignition.
2. The ceramic dry granular glaze according to claim 1, characterized in that: The chemical composition of the jade dry particles includes, by weight percentage, 56.00-61.00% of SiO2, 16.00-18.00% of Al2O3, 0.01-0.03% of Fe2O3, 0.01-0.05% of TiO2, 1.50-2.50% of CaO, 1.00-2.00% of MgO, 3.50-4.50% of K2O, 3.50-4.50% of Na2O, 0.05-0.20% of ZrO2, 2.50-3.50% of ZnO, 6.50-9.00% of BaO, 1.00-2.00% of SrO, and 0.05-0.20% of loss on ignition.
3. The ceramic dry particle glaze according to claim 1, characterized in that: The mass ratio of the jade-like dry particles to the color-changing dry particles is (7-22):
1.
4. The ceramic dry granular glaze according to claim 1, characterized in that: The silver halide is AgBr or AgI.
5. The ceramic dry granular glaze according to claim 1, characterized in that: The preparation steps of the jade dry particles include: The raw materials for preparing the jade dry particles are mixed, melted at 1400-1450° C. for 8-10 hours, poured into water for quenching to obtain jade frit particles, and crushed to obtain the jade dry particles; And / or, the preparation step of the color-changing dry particles includes: mixing the raw materials for preparing the color-changing dry particles, melting at 1300-1400° C. for 8-10 hours, pouring into water for quenching to obtain color-changing frit particles, and crushing to obtain the color-changing dry particles.
6. The ceramic dry particle glaze according to claim 5, characterized in that: The particle size of the jade-like dry particles is between 58-106 μm; and / or the particle size of the color-changing dry particles is between 45-75 μm.
7. A ceramic tile, characterized in that: From bottom to top, it includes a body layer, a surface glaze layer, a pattern layer, a dry particle glaze layer and a protective glaze layer. The dry particle glaze layer includes a color change area and a jade area. The color change area is formed by firing the ceramic dry particle glaze according to any one of claims 1 to 6; the jade area is formed by firing the jade dry particles.
8. The ceramic tile according to claim 7, characterized in that: The color change areas are distributed in the jade area in the form of dots, lines or blocks.
9. A method for preparing a ceramic tile according to claim 7 or 8, characterized in that: The following steps are involved: Taking the raw material of the green body layer to obtain the green body layer; Mixing jade dry particles, color-changing dry particles, glue and water to obtain color-changing dry particle glaze slurry; Mixing jade dry particles, glue and water to obtain jade dry particle glaze slurry; Respectively taking raw materials of the surface glaze layer and the protective glaze layer to prepare the surface glaze slurry and the protective glaze slurry; The surface glaze slurry is applied on the surface of the green body layer in sequence, a pattern is inkjet printed, the jade-like dry granular glaze slurry, the color-changing dry granular glaze slurry and the protective glaze slurry are applied, and after drying and firing, the ceramic tile is obtained.
10. The method for preparing a ceramic tile according to claim 9, characterized in that: The maximum sintering temperature is 1170-1210° C.; and / or the sintering period is 55-65 minutes.
Citation Information
Patent Citations
Method for preparing jadeite microcrystal glass ceramic composite board
CN102584351A
Ceramic glaze capable of discoloring along with light, ceramic tile capable of discoloring along with light and preparation methods thereof
CN110342959A
Decorative pattern photochromic ceramic tile and preparation method thereof
CN110436936A
Photochromic ceramic tile and preparation method thereof
CN110981198A
Jade glaze ceramic plate, preparation method and application thereof, and composition for preparing jade glaze
CN117185659A
